It is currently 24 Jun 2017, 10:58

### GMAT Club Daily Prep

#### Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

# Events & Promotions

###### Events & Promotions in June
Open Detailed Calendar

# x not equal to 0 x=sqrt(4xy-4y^2) then in terms of y, x= a)

Author Message
Director
Joined: 06 Feb 2006
Posts: 897
x not equal to 0 x=sqrt(4xy-4y^2) then in terms of y, x= a) [#permalink]

### Show Tags

21 Feb 2006, 12:07
1
This post was
BOOKMARKED
This topic is locked. If you want to discuss this question please re-post it in the respective forum.

x not equal to 0 x=sqrt(4xy-4y^2) then in terms of y, x=

a) 2y
b) y
c) y/2
d) -4y^2/(1-2y)
e) -2y
Manager
Joined: 16 Sep 2005
Posts: 62

### Show Tags

21 Feb 2006, 12:15
1
KUDOS
SimaQ wrote:
x not equal to 0 x=sqrt(4xy-4y^2) then in terms of y, x=

a) 2y
b) y
c) y/2
d) -4y^2/(1-2y)
e) -2y

I would go with A (2Y). Explaination as follows.
Given: x=sqrt(4xy-4y^2) and X <> 0
Squaring both the sides of the equation we get
X^2 = 4XY -4Y^2
So X^2 - 4XY + 4Y^2 = 0
Solving this equation we get
(2Y - X)(2Y - X) = 0
So X = 2Y

I hope this makes sense
_________________

Thanks

Senior Manager
Joined: 11 Jan 2006
Posts: 269
Location: Chennai,India

### Show Tags

21 Feb 2006, 22:30
me to A , but i tried back tracking.. substituted the values from the answers in the equation and only A solved

x = 2y , then from the stem x^2 = 4xy-4y^2 , if x=2y then
4y^2 = 4(2y)y - 4y^2= 8y^2-4y^2=4y^2

thus proved
_________________

vazlkaiye porkalam vazltuthan parkanum.... porkalam maralam porkalthan maruma

GMAT Club Legend
Joined: 07 Jul 2004
Posts: 5043
Location: Singapore

### Show Tags

21 Feb 2006, 22:33
x^2 = 4xy - 4y^2
x^2 - 4xy + 4y^2 = 0
(x-2y)^2 = 0
x = 2y
21 Feb 2006, 22:33
Display posts from previous: Sort by